Stimulation Dance Creations Art On Gross Motor Development Children Aged 5-6 Years in Islamic Al-Huda TK Semarang - Safitri, Nuril; Eka Nugroho, R Agustinus Arum (Universitas Negeri Semarang, 2017)
The purpose of this research is to determine the influence of dance creations art towards children aged 5-6 years gross motor development in the Al-Huda Islamic Kindergarten Semarang. This study uses a quantitative approach with methods Pre - Experimental Design in the form of one group pretest and posttest design . The population in this study were all students Kindergarten Al-Huda Islamic Semarang. Samples are students aged 5-6 years with 30 students at the Islamic Al-Huda TK Semarang based sampling using purposive sampling. Based on research and Paired Sample t-test was done, it can be concluded that there are differences after stimulation given dance creations on gross motor development of children aged 5-6 years in kindergarten Islam Al-Huda Semarang with t_hitung values ​​obtained with a value of -15.082 sig ( 2-tailed) 0.000 < 0.05, which means that there are significant differences between the pretest and posttest. Obtained a mean of -19.867. These results indicate that an increase in gross motor development of children with stimulation of dance creation, after to treatment in the experimental group, accumulation pretest scores are accumulated in 2164 and posttest score is 2760 with an increase in overall score was 596, or about 27.54% of the pretest scores.